2013
DOI: 10.1007/s10096-013-1934-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of the hormetic effect of disinfectants chlorhexidine, povidone iodine and benzalkonium chloride

Abstract: The study of the dose-response relationship of disinfectants is of great importance in treating infection, the objective being to use concentrations above the minimal bactericidal concentration (MBC). Below these concentrations, the bacteriostatic or bactericidal effect may be insufficient. Moreover, at low concentrations, a hormetic effect may be observed, producing a stimulation of growth instead of inhibitory action. Hormesis is not well known in the context of antimicrobial substances. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In addition, chlorhexidine, which is in general use for treating peri‐implantitis, may present some problems, because it is not effective and can enhance the growth of P. aeruginosa at some low concentrations (Morales‐Fernández et al. ). A microbiological analysis should be considered when designing peri‐implantitis therapy and further studies are needed to assess the role of opportunistic flora in these infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, chlorhexidine, which is in general use for treating peri‐implantitis, may present some problems, because it is not effective and can enhance the growth of P. aeruginosa at some low concentrations (Morales‐Fernández et al. ). A microbiological analysis should be considered when designing peri‐implantitis therapy and further studies are needed to assess the role of opportunistic flora in these infections.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the possibility that the periimplant pockets might be colonized by pathogens other than anaerobic periodontal flora. In vitro studies have identified the high affinity of P. aeruginosa (Truong et al 2010), S. aureus (Truong et al 2010) and yeast (do Nascimento et al 2013) for titanium surfaces. Some of these pathogens can cause early post-surgical infections (Cobo et al 2011;D'Ovidio et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OD value was recorded at 650 nm Every hour for nine hand marked as A t ( t = 1, 2, 3, 4, 5, 6, 7, 8, 9). Bacterial algebra (g) and growth rate ( μ ) were calculated by absorbance: 23 G=lnAt/A0/ln2, μ=lnAt/At1. …”
Section: Methodsmentioning
confidence: 99%
“…As a broad‐spectrum fungicide that against most bacteria, fungi, and viruses, iodine showed excellent advantages like high efficiency, low toxicity, cheap, and no drug resistance, and so forth . However, the iodine is not stable and difficult to store in a solvent or creams, and the iodine is easily sublimated and decomposed when in use, which could lead to the reduction of effective iodine content, shorten of efficacy time, and difficulties in controlling the dose .…”
Section: Introductionmentioning
confidence: 99%